Answer to Question #11459 in Trigonometry for vishesh
(cosA-sinA+1) / (cosA+sinA-1) = cosecA+cotA
1
2012-07-05T09:48:53-0400
Prove
(cosA-sinA+1) / (cosA+sinA-1) = cosecA+cotA
1 - cos^2 A = sin^2 A
=> (1 - cosA) * (1 + cosA) = sinA * sinA
=> (1 + cosA) / sinA = sinA / (1 - cosA)
=> (1 + cosA - sinA) / (sinA - 1 + cosA) = (1 + cosA) / sinA = 1/sinA + cosA/sinA
... [because a/b = c/d => (a-c)/(b-d) = a/b]
=> (cosA - sinA + 1) / (cosA + sinA - 1) = cosecA + cotA.
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment